Quantitative Wood Anatomy—Practical Guidelines - von Arx, Georg; Crivellaro, Alan; Prendin, Angela L.; Čufar, Katarina; Carrer, Marco (Frontiers in Plant Science, 2016)
Quantitative wood anatomy analyzes the variability of xylem anatomical features in trees, shrubs and herbaceous species to address research questions related to plant functioning, growth and environment. Among the more frequently considered anatomical features are lumen dimensions and wall thickness of conducting cells, fibers and several ray properties. The structural properties of each xylem anatomical feature are mostly fixed once they are formed, and define to a large extent its functionality, including transport and storage of water, nutrients, sugars and hormones, and providing mechanical support. The anatomical features can often be localized within an annual growth ring, which allows to establish intra-annual past and present structure-function relationships and its sensitivity to environmental variability. However, there are many methodological obstacles to overcome when aiming at producing (large) data sets of xylem anatomical data. Here we describe the different steps from wood sample collection to xylem anatomical data, provide guidance and identify pitfalls, and present different image-analysis tools for the quantification of anatomical features, in particular conducting cells. We show that each data production step from sample collection in the field, microslide preparation in the lab, image capturing through an optical microscope and image analysis with specific tools can readily introduce measurement errors between 5 to 30% and more, whereby the magnitude usually increases the smaller the anatomical features. Such measurement errors – if not avoided or corrected – may make it impossible to extract meaningful xylem anatomical data in light of the rather small range of variability in many anatomical features as observed, for example, within time series of individual plants. Following a rigid protocol and quality control as proposed in this paper is thus mandatory to use quantitative data of xylem anatomical features as a powerful source for many research topics.